The effect of aromatase inhibitors against possible testis toxicity in pembrolizumab treated rats - Turkmen, Nese Basak; Ciftci, Osman; Taslidere, Asli; Aydin, Muhterem; Eke, Binay Can (Wiley, 2022)
Pembrolizumab is a monoclonal antibody. Anastrozole is an infertility inhibitor of aromatase. Resveratrol is an antioxidant polyphenol in the reproductive system. This study was planned to demonstrate the protective effects of anastrozole and resveratrol against pembrolizumab-induced reproductive damage. Forty-two Sprague-Dawley rats were used in the study. Groups: The control, Pembrolizumab (PEMB), PEMB + Anastrazol (ANAST), PEMB + Resveratrol (RES), RES, and ANAST groups. At the end of the experiment, rats were euthanased under anaesthesia. Tissue samples were taken from rats for biochemical, histological, and ELISA evaluations. Tissues were subjected to routine tissue follow-up for histological analysis. Biochemically, thiobarbituric acid reactive substance (TBARS), glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) levels were measured. Sperm motility, abnormal sperm rate, and epididymal sperm concentration were examined spermatologically. Serum testosterone and programmed cell death-1 (PD-1) levels were measured using the ELISA. TBARS levels were significantly increased and GSH, SOD, GPx, and CAT levels were mitigated in PEMB-treated rats. Histologically; Control, ANAST, and RES groups testis samples were observed with normal histological appearance. Histological damage was detected in seminiferous tubule structures in testicular tissue in the PEMB group. In treatment groups, this damage was decreased. In addition, PD-1 and testosterone levels were evaluated by the ELISA method. ANAST and RES have therapeutic effects against reproductive damage caused by PEMB.
Keywords: anastrozole; pembrolizumab; resveratrol; testis